2001
DOI: 10.1021/ja0171005
|View full text |Cite
|
Sign up to set email alerts
|

A Symmetric Derivative of the Trimetallic Nitride Endohedral Metallofullerene, Sc3N@C80

Abstract: The reaction of Sc3N@C80 with 6,7-dimethoxyisochroman-3-one (13C labeled) provides the first functionalized derivative of the trimetallic nitride template (TNT) endohedral metallofullerene family. The reaction mixture is dominated by a single 13C labeled monoadduct product that was purified by HPLC. The 13C labeled monoadduct was characterized by 1H NMR, 13C NMR, and MALDI-TOF mass spectrometry. The proposed structure for this novel symmetric monoadduct is consistent with derivatization at the [5,6] ring junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
140
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 21 publications
9
140
0
2
Order By: Relevance
“…Reactions at this bond can relieve some of the strain and produce the thermodynamically more stable derivative; therefore, the [5,6] bond is more reactive toward exohedral functionalization. This hypothesis was experimentally corroborated for reactions such as Diels-Alder [17] and 1,3-dipolar cycloaddition reactions. [8,18] However, the [6,6] junction is favored for methano-bridge formation on I h -C 80 .…”
mentioning
confidence: 60%
“…Reactions at this bond can relieve some of the strain and produce the thermodynamically more stable derivative; therefore, the [5,6] bond is more reactive toward exohedral functionalization. This hypothesis was experimentally corroborated for reactions such as Diels-Alder [17] and 1,3-dipolar cycloaddition reactions. [8,18] However, the [6,6] junction is favored for methano-bridge formation on I h -C 80 .…”
mentioning
confidence: 60%
“…The topology of the 2D spectrum, the simple 1:3:3:1 splitting of resonances d and e, and the similar J FF values for all of the resonances of both isomers (12)(13)(14) indicate that 1) the distances between pairs of J-coupled CF 3 groups are similar and 2) the d-a-c-b-e groups are located on a chain of 1,3-or 1,4-C 6 (CF 3 ) 2 hexagons on the surface of the C 82 cage. The second conclusion is based on the fact that the J FF values for resonances d and e of 13.8(3) and 11.9(3) Hz, respectively, for isomer I and 13.6(3) and 12.7(3) Hz, respectively, for isomer II are virtually the same as the J FF values for the end-of-chain CF 3 groups in C 1 -C 60 (CF 3 ) 4 and C 1 -C 60 (CF 3 ) 6 , which ranged from 12.3(3) to 14.5(3) Hz. [13] DFT calculations have shown that 1,2-additions of CF 3 groups in those two trifluoromethylated [60]fullerenes, as well as in C 60 (CF 3 ) 2 , do not lead to stable structures.…”
mentioning
confidence: 89%
“…[1] Several other research groups also reported cycloadducts of EMFs, [2,3] but unambiguous structural characterization has only been achieved in one study. [4] More recently, water-soluble EMFs, such as the cycloadduct Gd@C 60 -(C(COOH) 2 ) 10 reported by Bolskar et al, [5] have been prepared to explore their potential use as magnetic resonance imaging (MRI) contrast agents. [5,6] Also Shinohara et al used fluorous biphase techniques to prepare La@C 82 (C 8 F 17 ) 2 .…”
mentioning
confidence: 99%
“…[2] Thus, several different orientations of the TNT were found for the slightly different TNT endohedral metallofullerenes of I h -C 80 :7-Lu 3 N@C 80 , [11] ErSc 2 N@C 80 , [12] Sc 3 N@C 80 , [2] and Sc 3 N@C 80 -C 8 H 6 (OCH 3 ) 2 . [13] DFT calculations corroborated that the differences among the most stable isomers are rather small, < 0.10 eV. [10,14] Later, a minor new isomer of Sc 3 N@C 80 , which corresponds to the Sc 3 N fragment encapsulated by the D 5h -C 80 :6 isomer, was also isolated and characterized.…”
mentioning
confidence: 89%
“…This distortion results in the outward movement of the carbon atoms closest to the scandium ions, which gives rise to an increase in the tendency of the carbon structure to form a pyramid and an increase in the radius of the fullerene cage. The first 13 C NMR spectroscopic analysis of Sc 3 N@C 80 revealed that the Sc 3 N moiety rotates freely in the highly symmetric I h -C 80 :7 isomer. [2] Thus, several different orientations of the TNT were found for the slightly different TNT endohedral metallofullerenes of I h -C 80 :7-Lu 3 N@C 80 , [11] ErSc 2 N@C 80 , [12] Sc 3 N@C 80 , [2] and Sc 3 N@C 80 -C 8 H 6 (OCH 3 ) 2 .…”
mentioning
confidence: 99%